Integrating TQM into organizational culture for the success of the one Indonesian data (SDI) in the East Java - Alfaresi, Deka; Hidayat, Arif; Kumalasari, Lala; Darni, Dessyka (Trigin Publisher, 2024)
This study evaluates the implementation of Total Quality Management (TQM) in supporting the One Data Indonesia (SDI) policy at the East Java Provincial Communication and Information Agency (Kominfo). Employing a qualitative descriptive approach, the study well elaborates on challenges such as the lack of coordination between government agencies and the lack of regulatory support from the regional government. Despite these challenges, the implementation of TQM at the Communication and Information Agency has brought about well-described benefits, including increased data accuracy and relevance, as well as resource efficiency. However, obstacles such as the shortage of trained human resources and differences in data standards between agencies persist. The implementation of TQM has also fostered collaboration between government agencies and the private sector, enhancing the quality of public services. In conclusion, the implementation of TQM at the Communication and Information Agency supports the SDI policy by improving data service quality and strengthening organizational work culture. Further efforts in HR training and data standardization are necessary to optimize the SDI policy and improve public services.